Sciencie, University and Society: Contributions and challenges for a critical public communication of science - Vignale, Julieta (Re-presentaciones: Periodismo, comunicación y sociedad, 2021)
This text aims to reflect on the public communication of science (CPC) as a discipline and its implications within the scientific community towards society. In these lines, dialogues and theoretical trajectories are approached through some referent authors of the field of study, which allow to make visible existing tensions. It is essential to analyze the traditional conception of audiences and the objectives of the ‘why’ communicating science. This reflection is developed from the theoretical approaches on public communication of science and its current challenges in the framework of professionalization and development of the STI field (Science, Technology and Innovation), to consider the links between science in the university and the challenge of Social Sciences, as a transformative discipline, as a contribution to the critical perspective in Latin American societies.